Applications of three-dimensional printing in orbital diseases and disorders. Issue 5 (September 2019) - Ruiters, Sébastien; Mombaerts, Ilse
Abstract : Purpose of review: To comprehensively review the applications of advanced three-dimensional printing technology in the management of orbital abnormalities. Recent findings: Three-dimensional printing has added value in the preoperative planning and manufacturing of patient-specific implants and surgical guides in the reconstruction of orbital trauma, congenital defects and tumor resection. In view of the costs and time, it is reserved as strategy for large and complex craniofacial cases, in particular those including the bony contour. There is anecdotal evidence of a benefit of three-dimensional printing in the manufacturing of prostheses for the exenterated and anophthalmic socket, and in the fabrication of patient-specific boluses, applicators and shielding devices for orbital radiation therapy. In addition, three-dimensional printed healthy and diseased orbits as phantom tangible models may augment the teaching and learning process of orbital surgery. Summary: Three-dimensional printing allows precision treatment tailored to the unique orbital anatomy of the patient. Advancement in technology and further research are required to support its wider use in orbital clinical practice.